HEGEMONI KEKUASAAN DALAM NOVEL LAUT BERCERITA KARYA LEILA S. CHUDORI - Taufiqi, Achmad Rizal; Kasnadi; Astuti, Cutiana Windri (Jurnal Bahasa dan Sastra, 2021)
Literature is a work that built by the author based on his/her social sensitivity of environment. This makes literature has various perspectives. One of them is inserting the ideological element in the structure of literary works. The transfer of ideology through hegemony makes people different from one and another. Likewise, in the novel LautBercerita by Chudori, which tells the story of a life conflict realized in ideological differences. The purpose of this research is to describe the ideology of authoritarianism and democratic contained in the novel LautBercerita. The method used in this research was descriptive qualitative, designed as literature review. The theory of Salamini on ideology was used to analyze the findings. The result of study showed that the novel depicted the ideology of authoritarianism and democratic which covered: i) elements of consciousness, ii) material elements, iii) elements of solidarity-identity and iv) elements of freedom.